A deficiência pelo olhar dos "normais" - Nardi, Laura Cristina (2008)
This research studies the social representations about the mental deficiency according to laypeople s point of view, people who do not have familiar or professional contact with people with mental deficiency. The study was based through data collected in a semistructured interview and activity of free association made in a square in a city of Rio Grande do Sul state. The subjects of the research were people who were passing by on the square and where asked to answer some questions. The data was organized into five categories and analyzed having as base the Barding Analysis of Content. This work focus the relationship with the people with mental deficiency versus the ones considered normal or regular according to the narratives of subjects with mental deficiency.It is questioned the concept of mental deficiency and the impact of the inclusion policy in the society. Contrasting the data obtained with the ones presented in the literature, the study allows the existence of a belittled representation with the people with mental deficiency